1988
DOI: 10.1136/sti.64.4.280-d
|View full text |Cite
|
Sign up to set email alerts
|

Cryotherapy compared with trichloroacetic acid in treating genital warts

Abstract: Letters should not exceed 400 words and should be typed double spaced (including the references) and be signed by all authors TO THE EDITOR, Genitourinary Medicine Fewer Trichomonas vaginalis organisms in vaginas of infected women during menstruation Sir, A recent paper by Demes et al reports lower counts of Trichomonas vaginalis organisms in the vagina during menstruation.' The authors considered that this was caused by immunological factors within menstrual blood. Other explanations for this result could als… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…In a study by Taner et al in Turkey, 51 patients with genital warts were treated with 85% TCA, and all patients had good treatment responses to TCA (14). Godley et al treated patients with warts with TCA in England in 1988 and reported good treatment efficacy and few complications (15). The present study compared the effects of CO 2 laser and trichloroacetic acid in the treatment of warts in patients who visited Khanevadeh Hospital from October 2013 to October 2014.…”
Section: Introductionmentioning
confidence: 90%
“…In a study by Taner et al in Turkey, 51 patients with genital warts were treated with 85% TCA, and all patients had good treatment responses to TCA (14). Godley et al treated patients with warts with TCA in England in 1988 and reported good treatment efficacy and few complications (15). The present study compared the effects of CO 2 laser and trichloroacetic acid in the treatment of warts in patients who visited Khanevadeh Hospital from October 2013 to October 2014.…”
Section: Introductionmentioning
confidence: 90%